Mexico's Illicit Drug Networks and the State Reaction - Jones, Nathan P. (Book collections on Project MUSE., 2016)
This study examines illicit drug networks in Mexico and explains why the state targets certain types of networks more forcefully than others. Jones classifies drug networks into two basic types, "territorial" and "transactional" networks. Transactional networks focus on trafficking and are more likely to collude with the state through corruption. Territorial networks, which seek to control territory for the purpose of taxation, extortion, and their own security, trigger a strong backlash from the state. They encroach upon the state's most fundamental functions--the ability to tax and provide security. Jones uses this typology to discuss how state response impacts the resilience of drug networks and what consequences this dynamic will have for Mexico and the ongoing battle between the territorial network, Los Zetas, and their transactional rivals, the Sinaloa Cartel. In addition to extensive archival research, Jones also conducted a year of fieldwork in Mexico City and Tijuana where he built his case study of the Arellano Felix Organization, through in-depth interviews with key figures from Mexican law enforcement, civic leaders, scholars, and organized crime victims